PCR mediated recombination impacts the analysis of hepatitis B Virus covalently closed circular DNA. Issue 1 (December 2016) - Suspène, Rodolphe; Thiers, Valérie; Vartanian, Jean-Pierre; Wain-Hobson, Simon
Abstract Background The replication of HBV involves the production of covalently closed circular DNA (cccDNA) from the HBV genome through the repair of virion relaxed circular DNA (rcDNA) in the virion. As cccDNA is the transcription template for HBV genomes, it needs to be eliminated from hepatocytes if the eradication of chronic HBV infection is to be achieved. PCR quantitation of cccDNA copy number is the technique of choice for evaluating the efficiency of treatment regimens. The PCR target commonly used to identify cccDNA spans the gapped region of rcDNA and is considered to accurately distinguish between cccDNA and rcDNA. There is however, a potentially confounding issue in that PCR can generate larger targets from collections of small DNA fragments, a phenomenon known as PCR recombination. Results The impact of PCR recombination towards the amplification of this cccDNA specific target was explored by mixing three marked, yet overlapping HBV DNA fragments. Thirteen of sixteen possible recombinants were identified by sequencing with frequencies ranging from 0.6 to 23%. To confirm this finding in vivo, HBV positive sera were treated with DNase I and submitted to quantitative real-time PCR. Under these conditions, it was possible to amplify the cccDNA specific segment without difficulty. As the virion contains uniquely rcDNA, amplification of the cccDNA target resulted from PCR recombination. Conclusions PCR quantitation of cccDNA may be more difficult than hitherto thought. Current detection protocols need to be investigated so as to help in the management of chronic HBV infection.